Faktor-faktor Yang Berhubungan Dengan Kejadian Karies Gigi Pada Anak di SD Negeri Bener 4 Ngrampal Sragen - Muhammad Sowwam; Pramita Ran Lestari (Politeknik Insan Husada Surakarta, 2023)
Background. Unhealthy teeth and mouth can affect a child's development, because the condition of the baby teeth will determine the growth of a child's permanent teeth. In addition, if a child has unhealthy teeth, he will find it difficult to digest food so that the child's growth process will be disrupted. As a result, children will easily catch disease. Preliminary study showed that 34 students at SDN 4 Bener Ngrampal Sragen had dental caries. Purpose. To find out the factors that influence the incidence of dental caries in children at SD Negeri Bener Ngrampal Sragen. Methods.. This research is a quantitative study with a cross sectional approach. The population in this study were 65 children from SD Negeri Bener 04, Ngrampal, Sragen. Samples were taken totaling 43 people with simple random sampling technique. Data was collected in November 2022. The independent variables explored were knowledge, habit of brushing teeth and diet. Data analysis was performed with univariate and multivariate analysis with logistic regression. Result.he results of the multivariate analysis using the logistic regression test showed that there was a significant effect (p<0.05) for the tooth brushing habit variable (p=0.042), there was no significant effect (p<0.05) for the knowledge variable (p=0.988) and no there was a significant effect on the diet factor (p=0.527). Conclusion: The knowledge factor had no effect on the incidence of dental caries, the habit of brushing teeth had an effect on the incidence of dental caries and the diet factor had no effect on the incidence of dental caries. Key words : dental caries, elementary school children